PEMANFAATAN UMBI PORANG SECARA KOMPLEKSITAS SEBAGAI BAHAN OBAT ALAMI DALAM MENURUNKAN KOLESTROL, PENYERAPAN KALSIUM, DAN PENANGANAN TERHADAP PENYAKIT DIABETES - Purnamawati, Ni Komang Sinta (Usadha, 2022)
Porang tubers as medicinal ingredients from nature, in the treatment of cholesterol, diabetes and high calcium in the blood. The presence of calcium oxalate in tubers makes it less favorable for direct consumption. Glucomannan, consisting of -1,4 linked D-mannose and D-glucose monomers, has been used in a variety of applications including food additives, pharmaceuticals, and the chemical industry. The method of this research is to carry out a descriptive type of approach based on observational support supported by a study of supporting literature that is relevant to the case study. From the identification of porang tubers as ingredients of traditional medicine, it can be concluded that about 43.99% glucomannan which is a specific carbohydrate in the form of processed flour is found in porang tubers. This tuber is used as an alternative food for carbohydrates because it can prevent the absorption of blood glucose and increase its levels making it suitable for diabetics, as well as excessive calcium absorption. Keywords: Umbi porang, Cholesterol, Diabetes, Hypercalcemia